Pengaruh Kesehatan Keselamatan Kerja, Beban Kerja, dan Gaji Terhadap Motivasi Kerja: Studi pada Karyawan Badan Penanggulangan Bencana Daerah Kota Pasuruan - Afifuddin Wahyu Anandita; Eko Agus Alfianto; Nueraeni (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of this research is to determine and measure the influence of Occupational Health and Safety, Workload and Salary on Work Motivation in Pasuruan City disaster management agency employees. This research is a quantitative study with a sample size of 86 respondents using a purposive sampling technique with an analysis tool, namely SPSS version 25. The results of the research show that Occupational Health and Safety has a significant effect on Work Motivation, Workload has a significant effect on Work Motivation, Salary has a significant effect on Work Motivation , Occupational Health, Safety, Workload, and Salary have a significant effect on Work Motivation.